Pulsatile Tinnitus due to a Tortuous Siphon-Like Internal Carotid Artery Successfully Treated by Arterial Remodeling - Dirk De Ridder; Sven Vanneste; Tomas Menovsky (Case Reports in Otolaryngology)
A patient is described with a right-sided tortuous siphon-like extracranial internal carotid artery leading to highly distressing ipsilateral heart beat synchronous pulsatile tinnitus, scoring 9/10 measuring loudness. Dilating the balloon during the occlusion test in or distal to the siphon-like anomaly reduces the arterial pulsations. Subsequently, surgery is performed using Teflon as an external construct to straighten the siphon-like anomaly. Postoperatively, the pulsations improve to 5/10 in a standing position and disappear during a reclined position. By adding a hearing aid, the pulsations are almost completely gone during a standing position (1/10) and remain absent in a reclined position.